Chromosome translocations in turtles: a biomarker in a sentinel animal for environmental biodosimetry - Ulsh, Brant A., author; Whicker, F. Ward, advisor; Bedford, J. S., advisor; Hinton, T. G., committee member; Lauenroth, W. K., committee member; Rowan, David, committee member (Colorado State University. Libraries, 2000)
This dissertation details a new approach for determining the magnitude and genetically relevant effects of wildlife exposures to radionuclides in contaminated environments. The yellow-bellied slider turtle (Trachemys scripta) served as a model organism. A biomarker of radiation exposure, the frequency of symmetrical chromosome aberrations in T. scripta lymphocytes, was developed which correlates with cumulative lifetime exposure. A fluorescence in situ hybridization probe for T. scripta chromosome-1 was constructed through microdissection and amplification by polymerase chain reaction. The T. scripta probe hybridized exclusively to chromosome-1 T. scripta, and in each of four other turtle species, demonstrating conservation of chromosome-1 homology in turtles over 66 million years. The efficacy of this probe in detecting radiation-induced chromosome aberrations was demonstrated through the construction of a dose-response curve for T. scripta fibroblasts acutely irradiated in vitro. With respect to induction of chromosome interchange aberrations, human fibroblasts are approximately 1.7 times more radiosensitive than the T. scripta fibroblasts. To move toward application of this biomarker in field studies, culture conditions for T. scripta lymphocytes, which can be sampled nonlethally, were developed. Since protracted exposures result in a reduced effect per unit dose, the extent of this effect for aberration induction in turtle cells was examined in both fibroblasts and lymphocytes. The dose-rate below which no reduction in effect per unit dose is observed with further dose protraction was approximately 23 cGy hr-1. The whole-genome spontaneous background level of complete, apparently simple symmetrical translocations in T. scripta lymphocytes, projected from aberrations occurring in chromosome-1 was approximately 1.20x10-3/cell. Comparable spontaneous background levels reported for humans are some 5- to 30-fold higher. This relatively low background level for turtles would be a significant advantage for measurement of effects at low doses and dose-rates. Finally, the dose-response of T. scripta lymphocytes irradiated in vivo at a low dose-rate was determined. The best fit curve was Y = (0.0015±0.0013) + (0.0058±0.0009)*D - (0.00033±0.00011)*D2; where Y = number of apparently simple symmetrical translocations per cell, D = dose (Gy), and errors are one Poisson standard deviation. This dose-response relationship can serve as a calibration curve for environmental biodosimetry field studies.
Keywords: ecology; cellular biology; environmental science; biophysics